STUDENTS SATISFACTION TOWARD GENERAL ENGLISH ONLINE CLASS - Jokosaharjo, Sulistyoadi; Julyanti, Ni Komang Paramitha (Akademi Komunitas MAPINDO, 2021)
Covid-19 has caused major changes in teaching-and-learning practice, one of them is the change from a conservative face-to-face in-class teaching and learning practice into an online class. This change has caused disturbances in the practice. The unreadiness both from the human resources and the technology become the main problems in conducting an online teaching-and-learning practice, therefore, it is interesting to find out the students’ perception toward the online teaching-and-learning practice. This research tried to find out the students’ satisfaction toward the online class of English General subject. The respondents were the students of tourism faculty and business faculty of Triatma Mulya University who were taking the English General subject in total of 94 students. The survey results show that the main hindrances in taking an online class are the internet bandwidth, signal stability, and data plan (internet quota). When the Covid-19 pandemic has ended, most of the students prefer to have the regular offline class, 3 students suggest to combine online and offline classes, and only 2 students prefer to have an online class. Keywords: Survey online class, satisfaction, Covid-19.